Answer:
-1/3x
Explanation:
Known :
- x1 = -3
- x2 = 0
- y1 = 1
- y2 = 0
Asked :
Solution :
We can find the straight line equation using this formula,
![(y-y1)/(y2-y1) = (x-x1)/(x2-x1)](https://img.qammunity.org/2023/formulas/mathematics/college/4161qin2pgcitqplda4sztijyfz3hyipaz.png)
Insert all we know inside the formula,
![(y-1)/(0-1) = (x-(-3))/(0-(-3))\\(y-1)/(-1) = (x +3)/(3)\\](https://img.qammunity.org/2023/formulas/mathematics/college/z5ectiw9fi3t8fesa4zqz6k5a3a49spbm3.png)
Use cross multiplication,
3(y - 1) = -1(x + 3)\
3y - 3 = -x - 3
3y = -x - 3 + 3
3y = -x
y = -1/3x
Conclusion :
The correct equation is y = -1/3x